2020
DOI: 10.3389/fgene.2020.00514
|View full text |Cite
|
Sign up to set email alerts
|

Combining High Oleic Acid Trait and Resistance to Late Leaf Spot and Rust Diseases in Groundnut (Arachis hypogaea L.)

Abstract: High oleic trait, resistance to rust and late leaf spot (LLS) are important breeding objectives in groundnut. Rust and LLS cause significant economic loss, and high oleic trait is an industry preferred trait that enhances economic returns. This study reports marker-assisted selection to introgress high oleic content, resistance to LLS and rust into Kadiri 6 (K 6), a popular cultivar. The alleles for target traits were selected using linked allele-specific, simple sequence repeats and single nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Another study using a different source performed whole genome sequencing of complete RIL population (Tifrunner × GT-C20) and identified major QTLs on chromosome A05 and B03 with phenotypic variance~47% in US germplasm [23]. These genetic mapping studies confirmed the genomic region on chromosome A03/B03 responsible for LLS resistance and the linked SSR/SNP markers [7] were used in marker assisted selection to develop LLS resistance varieties [9,[24][25][26].…”
Section: Introductionmentioning
confidence: 80%
“…Another study using a different source performed whole genome sequencing of complete RIL population (Tifrunner × GT-C20) and identified major QTLs on chromosome A05 and B03 with phenotypic variance~47% in US germplasm [23]. These genetic mapping studies confirmed the genomic region on chromosome A03/B03 responsible for LLS resistance and the linked SSR/SNP markers [7] were used in marker assisted selection to develop LLS resistance varieties [9,[24][25][26].…”
Section: Introductionmentioning
confidence: 80%
“…Currently, diagnostic markers are available in groundnut breeding for resistance to foliar fungal diseases, nematode, bacterial wilt, and high oleic acid, seed weight and fresh seed dormancy traits. Marker-assisted selection (MAS) approaches for different traits such as, nematode resistance [32], high oleic [11,13,19,23] and rust, and LLS [16][17][18] using diagnostic markers of various marker systems such as SSRs, ASP (allelespecific), AhMITE1 (A. hypogaea miniature inverted-repeat transposable element), and SNP markers are used by the groundnut breeding programs in India, the USA, and China. Through a cooperation agreement with Intertek-AgriTech, the HTPG project, directed by ICRISAT, intends to deliver low-cost, high-throughput genotyping services primarily for forward breeding applications [14].…”
Section: Discussionmentioning
confidence: 99%
“…Through a cooperation agreement with Intertek-AgriTech, the HTPG project, directed by ICRISAT, intends to deliver low-cost, high-throughput genotyping services primarily for forward breeding applications [14]. Deployment of a combination of SNP markers for pyramiding different traits provides cost-effectiveness by deploying MEGS to select desired lines [13,23]. MEGS reduces the population size manageable with limited resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected on kernel and haulm yields (KY and HY, respectively) from each plot and converted to tons per hectare (t ha −1 ). Oil yield in t ha −1 (OY = oil content in % times kernel yield in t ha −1 ), the contents of total oil (OC), total protein (TPC), palmitic acid (PAC), stearic acid (SAC), oleic acid (OAC), and linoleic acid (LAC) contents of the kernels were estimated using a Near Infrared Spectroscopy (NIRS; XDS monochromator, FOSS Analytical AB, Hillerød, Sweden; Deshmukh et al., 2020). Data on dry HY was collected and expressed in t ha −1 .…”
Section: Methodsmentioning
confidence: 99%